Effect Bottom Ash as Partial Substitute of Sand on Compression Strength of Concrete - Deni Susanti, Rika; Kesuma Hadi, Indra; Sitompul, Sahat; Shubhan, Ibnu (International Journal of Engineering and Technology, 2019)
This article presents a study on compression strength of concrete with bottom ash as partial substitute of sand. Initial testing was conducted with slump test of normal concrete and bottom ash-concrete. Further tests were performed with compressive strength test with 0%, 10%, 20%, 30%, and 40% of bottom ash each with concrete age of 14, 21, and 28 days. The next test performed on a specimen with 5%, 7.5%, 10%, and 12.5% of bottom ash. From each test variation, it was found that the potential of compressive strength achieved when sand was replaced by bottom ash. The result showed that the concrete mix with 10% bottom ash or smaller can be used as a substitute for sand in concrete mixes. Â Â